COMPARATIVE ANALYSIS OF KAZAKHSTANI EDUCATIONAL POLICIES AND PRACTICES AGAINST THE UNESCO POLICY GUIDELINES FOR INCLUSION IN EDUCATION (2009) - Нургазина, Асель Танатовна (My University, 2019)
Мақала инклюзивтік білім беру саласындағы Қазақстан мен ЮНЕСКО-ның саясатын жəне инклюзивті білім беруді дамытудың алғышарттарын жəне инклюзияны енгізудің негізін салыстырмалы талдауына арналған. Статья посвящена сравнительному анализу политики Казахстана и ЮНЕСКО в сфере инклюзивного образования, которая отражает предпосылки для развития инклюзивного образования в Казахстане и международную политику, как основу внедрения инклюзии. The article is devoted to comparative analysis of Kazakhstani and UNESCO policies for inclusion in education, which reflects the premises for the development of inclusive education in Kazakhstan, and international policies which are the basis of inclusion.
Keywords: инклюзия,; саясат; арнайы білім беру қажеттіліктері; бəріне арналған білім; алғышарт; бұзушылық; инклюзия; политика; специальные образовательные нужды; образование для всех; предпосылка; нарушение; inclusion; policy; special educational needs; education for all; premises; disorder